Morfološke značilnosti rogovja srnjadi (Capreolus capreolus L.) v populaciji v Škofjeloškem hribovju - Hafner, Miran (Gozdarski vestnik, 2004)
Morphological characteristics of roe deer antlers have been studied on a sample of 182 animals belonging to the population in the Škofjeloško hribovje area which were hunter-harvested in the period from 1980 to 2003 on an area ofapproximately 75 km2. 26 various traits have been measured. The majority of antler traits are in tight positive correlation. Negative correlation has beenascertained in the distance between the bases of antlers, the diameter of the base and skull width in connection with some other antler characteristics.Carcass mass reaches highest values at the age of 5 years, while antler mass reaches highest values at the age of 6 years. Carcass mass depends on age and month of shooting. The majority of antler traits which werestudied depend on age and carcass mass. If we exclude the influence of carcass mass, the mean values of the majority of traits studied differ among age classes - with the exception of the inside spread at the top of the main beams, the main beam length to front tine, the distance between pedicles, the height of bases on the front side, the height of pedicles and the length of the nasal bone. The majority of the traits studied which express the potency of antlers reach highest values in the middle age class. Because of the various changes of mean values of the traits studied, the relations between the mean values also vary with age. After the culmination of antler mass, the length of the main beams and pedicles and the circumference of the upper part of the main beam start to decrease. In the area of pedicles and bases the antlers tend to increase in spread as does the smallest inside spread. The ratio between smallest inside spread and greatest inside spread increases withage, while the distance from the point of the smallest inside spread to the point of the greatest inside spread on the main beam decreases. Missing tines would occur more frequently among younger and older age classes comparedto the middle age classes. We have not detected any differences between missing front and back tine. With age characteristic changes occur on antlers and upper part of skull which could be of help at assigning hunter-harvested animals into adequate age classes.
Keywords: lastnosti; morfologija; rogovje; srnjad; telesna masa